Synergistic Cationic–Anionic Regulation in Ni-Doped FeSe@C Anodes with Se Vacancies for High-Efficiency Sodium Storage - Liang Wang; Shutong Cai; Dingwen Wang; Xiangyi Wang; Yang Cheng (Batteries)
Sodium-ion batteries present an economical energy storage solution, yet their anode kinetics remain slow, impeding rate performance and cyclability. Layered FeSe anodes, characterized by metallic conductivity, hold potential, but structural decay and insufficient active sites during cycling continue to pose challenges. Herein, these challenges are addressed through the implementation of dual Ni doping and Se vacancy engineering in FeSe@C to synergistically regulate cationic/anionic configurations. The ionic substitution of larger Fe2+ ions (0.78 Å ionic radius) with smaller Ni2+ ions (0.69 Å) induces lattice distortion and generates abundant Se vacancies, enhancing electron transport, active site accessibility, and Na+ adsorption. These synergistic modifications effectively boost Na+ diffusion kinetics and electrolyte compatibility, creating a favorable electrochemical environment for fast sodium storage. Consequently, the optimized 2%Ni-FeSe@C electrode retains an exceptional discharge specific capacity of 307.67mAh g−1 after 1000 cycles at an ultrahigh current density of 5 Ag−1, showcasing superior rate capability and long-term cycling stability, paving the way for practical high-power SIBs.